Compression Load Tests on Composite Foundations of Spread Footing Anchored by Helical Anchors - Mingqiang Sheng; Zengzhen Qian; Xianlong Lu (Advances in Civil Engineering)
This study elucidates the compression behavior of a type of composite foundation of spread footing anchored by helical anchors. Three composite foundations were installed at a field site, and compression load testing was carried out on each foundation. Both the site conditions and the load tests were documented comprehensively. The compression load-settlement curves of composite foundations exhibit an initial linear-elastic segment, a curve transition, and a final linear region, and their capacities should be interpreted from the load-settlement curves. Five representative interpretation criteria (Chin, Terzaghi and Peck, slope tangent, tangent intersection, and L1–L2) were employed to determine the capacity of each foundation. Both the helical anchors and the footing share compression loadings on the composite foundation. Soil pressure cells at the center, near the edge, and at the corner of the footing represent a distribution from the lower, middle, and higher ranges of incremental soil pressures underneath the footing. Helical anchors underneath the footing approximately share 60%–80% of total load applied on the composite foundation pier, and higher compression resistance of a composite foundation can be obtained by increasing the footing embedment depth and the number of helical anchors underneath the footing.